Perencanaan pembelajaran Creative Learning dalam mata kuliah Profesi Keguruan - Beti Istanti Suwandayani; Siti Fatimah Soenaryo; Reny Dwi Susanti (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
Life in the millennial era requires a variety of skills that must be mastered by humans, so that education is expected to provide preparation for students to master the various skills. Achievement of skills in the 21st century can be done through renewal in the quality of learning. This study aims to analyze the implementation of planning, constraints in learning planning, and solutions in planning creative learning. The method used in this research is qualitative descriptive research. Data collection used is observation, interviews and documentation. This data collection technique uses instruments as guidelines for data collection. Data analysis in this study used descriptive analysis in the form of in-depth exposure related to this research data. The results of this study indicate that learning planning is carried out before learning by preparing learning tools in the form of course RPS. The problems that arise in planning this learning are integrating learning planning with millennial development. Whereas to overcome these problems in creative learning is to innovate media-making assistance and technology-based learning.